EFFICACY, SAFETY AND TOLERABILITY OF STREPTOKINASE IN MULTILOCULATED EMPYEMA - Khan, Nisar; Mian, Ihsanullah; Javed, Arshad; Wazir, Samad; Yousaf, Mohammad (Journal of Ayub Medical College Abbottabad, 2003)
Background: Empyema thoracis is a common illness with significant morbidity and mortality. Standard treatment of Empyema includes tube drainage and antibiotics. But the tube drainage often fails if the fluid is loculated. Intrapleural Streptokinase has been used in multiloculated empyemas with good success rate. We evaluated the efficacy and safety of intra-pleural Streptokinase in loculated empyemas. Methods: A total of 15 patients admitted in Pulmonology unit with multiloculated empyemas whose drainage via drainage tube was less than 100 ml during the last 24 hours were included in the study. Aliquots of 250,000 units of Streptokinase in 100 ml of normal saline were instilled into the pleural cavity and the tube clamped for 3 hours. Response was assessed by clinical outcome, measurement of drain output after unclamping and subsequent chest radiography and serial chest ultrasounds. Results: Streptokinase enhanced drainage in all patients with complete resolution of Empyema in 13 patients. Two patients with thickened visceral pleura following empyema drainage were referred to thoracic surgeon for decortication. The number of instillations of Streptokinase per patient ranged from 1 to 3 and the volume of drained empyema fluid ranged from 60 ml to 600 ml per patient. Streptokinase was well tolerated in all patients. Conclusion: Intrapleural Streptokinase is a safe and effective means of increasing the tube drainage in multiloculated Empyema without causing systemic fibrinolysis. Key Words: Streptokinase, Multiloculated Empyemas, Fibrinolysis.